Relevance Between Bloom’s Taxonomy and Neuner’s Übungstypologie in “Netzwerk A1” - Karina Awalia Bingesti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
This article describes the representation of the Bloom’s Taxonomy and the Neuner’s Typology of Exercises. According to the analysis results, a representation of Bloom's Taxonomy and Neuner’s Typology of Exercises are found the books of Netzwerk A1. Representations of the Bloom's Taxonomy are categorized in the cognitive, psychomotor, and affective domains. The exercises in the books of Netzwerk A1 have also represented the typology of communicative exercise.